Kontribusi Sektor Pertambangan terhadap Kesejahteraan Masyarakat: Analisis Kebijakan Publik di Kabupaten Lahat - Zetia Wijayanti; Pandu Pamungkas; Maelani Maelani; Anisa Bella; Angel Lauren; Dewi Eliza (MAN 4 Kota Pekanbaru, 2026)
Lahat Regency has significant economic potential in the mineral and coal mining sector, which is a major contributor to regional income and plays a crucial role in driving economic growth. This study aims to analyze the mining sector's contribution to improving community welfare in Lahat Regency by incorporating the policy implementation framework proposed by George C. Edward III. The research method employed a qualitative approach through literature study and secondary data analysis sourced from the Lahat Regency Government's Notes to Financial Reports (CaLK) and data from the Central Statistics Agency (BPS). The results show that the mining sector contributes the most to regional income, with a significant increase reaching 36.49% in 2023, and per capita income rising to Rp65.83 million per year. However, this increase has not been accompanied by a decrease in the poverty rate, with Lahat Regency still ranking second in terms of the number of poor people in South Sumatra Province. This condition indicates that the mining sector has not provided an equitable economic impact on the community.